Representations Of Female Friendship And Identity In And Just Like That... & Insecure - Anindya Amara Putri; Athaillah Cinta Notoprayitno; Bintang Farisqi Ardianta; I Made Bagus Vishwananda Paramartha (Social Sciences Journal, 2026)
This study compares how two HBO series, And Just Like That… (2021- ) and Insecure (2016-2021), represent female friendship and identity. Both shows focus on women, but they come from different cultural and social contexts. Using postfeminist theory (Gill, 2007) and intersectional feminism (Crenshaw, 1991; Collins, 1990), this research analyzes character development, dialogue, and storylines from selected episodes. The findings show that And Just Like That… emphasizes personal choice, lifestyle, and privilege, while Insecure highlights how race, gender, and class shape women’s everyday experiences. The study also shows that friendship works differently in each show: in And Just Like That…, it supports personal growth, while in Insecure, it represents solidarity and shared struggle. Together, the shows reveal two different ways of understanding modern womanhood on television.